Variability and typical error in the kinematics and kinetics of the maximal instep kick in soccer - Lees, A.; Rahnama, N. (Sports Biomechanics, 2013)
The purpose of this paper was to establish the variability and typical error of kinematic and kinetic variables representing the maximal instep kick in soccer for both the kicking and support legs. Ten skilled (good amateur or semi-professional) soccer players performed 20 maximal instep kicks of a stationary ball into a goal mouth. Motion of the kicking and support legs was recorded by an optoelectronic motion analysis system, and a six degrees of freedom model was used to compute kinematic and kinetic variables. Participants repeated the kicks on a second day at least 1 week later. The mean within-subject coefficient of variation across the kinematic and kinetic variables, trials, and days was 16% and did not change substantially as trial number increased or between day of test. Increasing trial number reduced the typical error (as determined by the standard error of the mean) such that for 20 trials 75% of the variables were below an arbitrary 5% threshold. It was concluded that for kicking investigations, 10-15 trials could be used and typical errors of 5% should be expected.